Sharia Accounting as An Information System - Dian Rohani Siburian; Syaloom lestari Simanjuntak; Ayu Ashari Pasaribu; Muhammad Ismail; Gio Qaedy Auzan; Meigia Nidya Sari (International Journal of Economic Research and Financial Accounting, 2025)
Sharia accounting as an information system plays a central role in supporting transparency and accountability in the management of finances based on Islamic principles. In this context, sharia accounting functions not only as a recording and reporting tool but also as a mechanism that integrates the moral and ethical values embedded in Islamic teachings. This study aims to explore how sharia accounting can serve as an effective information system, emphasizing the importance of honesty, justice, and social responsibility in every transaction. Through a qualitative approach and content analysis, this research reveals that sharia accounting seeks to deconstruct modern accounting practices that are often trapped in materialistic values. Instead, the sharia accounting information system provides a more humanistic framework, where each financial report is not merely numbers but also reflects the social and moral impact of business decisions. The findings indicate that the implementation of sharia accounting can enhance stakeholder trust and promote more sustainable business practices. Thus, this study asserts that sharia accounting as an information system is not just an administrative tool but a foundation for ethical and responsible decision-making in the business world. Sharia accounting offers innovative solutions to contemporary financial challenges while adhering to the principles of sharia that underpin all economic activities.